SUGAR-FREE, BUT NOT SYMPTOM-FREE: THE IMPACT OF ARTIFICIAL AND POLYOL-BASED SWEETENERS ON IBS AND GASTROINTESTINAL HEALTH - Weronika Stachera; Maciej Sobczyk; Julia Stępień; Barbara Wołoszyn; Julia Guzowska; Małgorzata Zach; Patrycja Rzeźnik; Aleksandra Borowy; Wiktoria Suchcicka; Aleksandra Chajnowska (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Objective: Irritable Bowel Syndrome (IBS) is a common gastrointestinal disorder significantly influenced by diet. In recent years, sugar-free products containing artificial sweeteners and polyols have become increasingly popular, especially among people with IBS. This article reviews the impact of these sweeteners on IBS symptoms and gut microbiota.Methods: This is a literature review based on articles from the PubMed database published between 2020 and 2025. Studies focusing on artificial sweeteners, polyols, and their effects on IBS and gut health were included.Results: The reviewed studies show that some artificial sweeteners and polyols can worsen IBS symptoms such as bloating, gas, and diarrhea. Additionally, they may negatively affect the gut microbiota, contributing to dysbiosis.Conclusion: Although promoted as healthier sugar substitutes, many sweeteners may be problematic for IBS patients. Their consumption should be individualized and approached with caution.